The Brain is Hypothermic in Patients with Mitochondrial Diseases. Issue 5 (May 2014) - Rango, Mario; Arighi, Andrea; Bonifati, Cristiana; Del Bo, Roberto; Comi, Giacomo; Bresolin, Nereo
We sought to study brain temperature in patients with mitochondrial diseases in different functional states compared with healthy participants. Brain temperature and mitochondrial function were monitored in the visual cortex and the centrum semiovale at rest and during and after visual stimulation in seven individuals with mitochondrial diseases ( n = 5 with mitochondrial DNA mutations and n = 2 with nuclear DNA mutations) and in 14 age- and sex-matched healthy control participants using a combined approach of visual stimulation, proton magnetic resonance spectroscopy (MRS), and phosphorus MRS. Brain temperature in control participants exhibited small changes during visual stimulation and a consistent increase, together with an increase in high-energy phosphate content, after visual stimulation. Brain temperature was persistently lower in individuals with mitochondrial diseases than in healthy participants at rest, during activation, and during recovery, without significant changes from one state to another and with a decrease in the high-energy phosphate content. The lowest brain temperature was observed in the patient with the most deranged mitochondrial function. In patients with mitochondrial diseases, the brain is hypothermic because of malfunctioning oxidative phosphorylation. Neuronal activity is reduced at rest, during physiologic brain stimulation, and after stimulation.